Blood glucose-lowering activity of protocatechuic acid is mediated by inhibiting α-glucosidase - Huafang Ding; Shouhe Huang; Chui Yiu Chook; Erika Kwek; Chi Yan; Kaying Ma; Jianhui Liu; Hanyue Zhu; Zhenyu Chen (Food Science and Human Wellness)
α-Glucosidase inhibitors are effective in controlling postprandial hyperglycemia, which play crucial roles in the management of type 2 diabetes. Protocatechuic acid (PCA) is one of phenolic acids existing not only in various plant foods but also as a major microbial metabolite of dietary anthocyanins in the large colon. The present study investigated the inhibitory mechanism of PCA on α-glucosidase in vitro and examined its effect on postprandial blood glucose levels in vivo. Results from in vitro experiments demonstrated that PCA was a mix-type inhibitor of α-glucosidase. Driven by hydrogen bonds and van der Waals interactions, PCA reversibly bound with α-glucosidase to form a stable α-glucosidase-PCA complex in a spontaneous manner. The computational simulation found that PCA could insert into the active cavity of α-glucosidase and establish hydrogen bonds with catalytic amino acid residues. PCA binding aroused the steric hindrance for substrates to enter active sites and caused the structural changes of interacted catalytic amino acid residues. PCA also exhibited postprandial hypoglycemic capacity in diabetic mice. This study may provide the theoretical basis for the application of PCA as an active ingredient of functional foods in dietary management of diabetes.